Obesity in patients with end-stage heart failure - Król, Bogumiła; Oprzędkiewicz, Aleksandra; Szczurek, Wioletta; Szyguła-Jurkiewicz, Bożena (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2018)
Obesity poses an increasing problem in patients with end-stage heart failure (HF). The most commonly used indicator of obesity is body mass index. The value of this parameter is widely taken into consideration when selecting the best way of treatment for patients with advanced HF. The aim of this paper is to outline the recent knowledge about obesity in the abovementioned group of patients.